Fundamental of air pollution - Vallero, Daniel A (Elservier, 2008)
The fourth edition will be updated to include numerous MACTs which were not foreseen during the writing of the third edition, such as secondary lead (Pb) smelting, petroleum refining, aerospace manufacturing, marine vessel loading, ship building, printing and publishing, elastomer production, offsite waste operations, and polyethylene terephthalate polymer and styrene-based thermoplastic polymers production.